Influence of Fluorinated Components on Perovskite Solar Cells Performance and Stability. Issue 8 (1st February 2021) - Ouedraogo, Nabonswende Aida Nadege; Yan, Hui; Han, Chang Bao; Zhang, Yongzhe
Abstract: Several valuable scientific investigations have been conducted these last few years in materials design and device engineering for perovskite solar cells (PSCs) to make them competitive compared to traditional silicon‐based photovoltaic technologies. Consequently, high power conversion efficiency beyond 25% is nowadays reported. However, their long‐term stability remains a significant challenge to overcome. Herein, the influence of fluorinated compounds on each layer of PSCs devices and their impact on the resulted device performances and stability is spotlighted. The fluorinated compounds exhibit attractive properties due to their very high electronegativity attributed to the fluorine atom, and their strong hydrophobicity. Thus, the introduction of these compounds is found to be a successful strategy to positively suppress the surface trap states, enhancing charge collection and reducing interfacial charge recombination. Besides, a better film quality and better energy level alignment is obtained, resulting in the improvement of device photovoltaic parameters such as the open‐circuit voltage ( V oc ), short‐circuit current ( J sc ), and fill factor (FF), and then, the device's overall power conversion efficiency (PCE). Their long‐term stability is also found to further be improved. Abstract : A systematic summary of the use of fluorinated compounds in each layer of perovskite solar cells is reviewed. Fluorinated compounds induce better electron and hole transporting material quality. The high electronegativity of the fluorine element allows an efficient charge‐extraction and transport at the perovskite surface and interfaces. More importantly, these fluorinated compounds greatly enhance both device efficiency and long‐term stability.